Development and Application of an Oral Challenge Mouse Model for Studying Clostridium perfringens Type D Infection - Fernandez Miyakawa, Mariano Enrique (2007)
Clostridium perfringens type D isolates cause enterotoxemia in sheep, goats, and probably cattle. While the major disease signs and lesions of type D animal disease are usually attributed to epsilon toxin, a class B select agent, these bacteria typically produce several lethal toxins. Understanding of disease pathogenesis and development of improved vaccines are hindered by the lack of a small-animal model mimicking natural disease caused by type D isolates. Addressing this need, we developed an oral challenge mouse model of C. perfringens type D enterotoxemia. When BALB/c mice with a sealed anus were inoculated by intragastric gavage with type D isolates, 7 of 10 type D isolates were lethal, as defined by spontaneous death or severe clinical signs necessitating euthanasia. The lethalities of the seven type D isolates varied between 14 and 100%. Clinical signs in the lethally challenged mice included seizures, convulsions, hyperexcitability, and/or depression. Mild intestinal gas distention and brain edema were observed at necropsy in a few mice, while histology showed multifocal acute tubular necrosis of the kidney and edema in the lungs of most challenged mice that developed a clinical response. When the lethality of type D isolates in this model was compared with in vitro toxin production, only a limited correlation was observed. However, mice could be protected against lethality by intravenous passive immunization with an epsilon toxin antibody prior to oral challenge. This study provides an economical new model for studying the pathogenesis of C. perfringens type D infections.